Environmental Chemistry - Hawker, Darryl (Griffith University, 2011)
Development and calibration of novel passive samplers for analytes of emerging interest.
Keywords: Environmental Chemistry (incl. Atmospheric Chemistry); 860600 - Industrial Chemicals and Related Products